2020
DOI: 10.1002/ange.202011203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Perovskite–Zeolite Composite Enabled by Encapsulation and In Situ Passivation

Abstract: Metal halide perovskites have been widely applied in optoelectronic fields, but their poor stability hinders their actual applications. A perovskite-zeolite composite was synthesized via in situ growth in air from aluminophosphate AlPO-5 zeolite crystals and perovskite nanocrystals. The zeolite matrix provides quantum confinement for perovskite nanocrystals, achieving efficient green emission, and it passivates the defects of perovskite by H-bonding interaction, which leads to a longer lifetime compared to bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The SiO 2 shell usually imparts better photostability to HP nanocrystals which is probably due to the suppressed migration of ions and vacancies. 46,47 The yolk-shell Cs 2 AgBiBr 6 @SiO 2 mesoporous sub-microspheres have great potential for photocatalysis in a polar solvent medium owing to their better thermal, light and water stability. The photocatalytic CO 2 reduction performance was measured in a mixed medium of acetonitrile and water under visible light irradiation (λ > 420 nm), with Co(bpy) 3 2+ (bpy = 2,2′-bipyridine) as a molecular cocatalyst and triethanolamine (TEOA) as a hole scavenger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SiO 2 shell usually imparts better photostability to HP nanocrystals which is probably due to the suppressed migration of ions and vacancies. 46,47 The yolk-shell Cs 2 AgBiBr 6 @SiO 2 mesoporous sub-microspheres have great potential for photocatalysis in a polar solvent medium owing to their better thermal, light and water stability. The photocatalytic CO 2 reduction performance was measured in a mixed medium of acetonitrile and water under visible light irradiation (λ > 420 nm), with Co(bpy) 3 2+ (bpy = 2,2′-bipyridine) as a molecular cocatalyst and triethanolamine (TEOA) as a hole scavenger.…”
Section: Resultsmentioning
confidence: 99%
“…The SiO 2 shell usually imparts better photostability to HP nanocrystals which is probably due to the suppressed migration of ions and vacancies. 46,47…”
Section: Resultsmentioning
confidence: 99%
“…The elemental ratio of Pb:Br is 1:2.63 survey by XPS, which is probably caused by loss of halogen. 31 These evidences demonstrate that the CsPbBr 3 NCs distributed tightly within the CMS template.…”
Section: Introductionmentioning
confidence: 90%
“…Figure S9 shows the TRPL spectra of CsPbBr 3 film and CsPbBr 3 @CMS, the decay curves of CsPbBr 3 film and CsPbBr 3 @CMS sample can be well fitted into multiexponential and triexponential equation, slow decay and fast decay are related with the excitonic recombination and the high trap density at the crystal surface, respectively (Table S1). 31 The average lifetime (τ ave ) of CsPbBr 3 NCs elongated from 12.28 to 19.16 ns after confinement growth in CMS. This kinetics test results indicated that much lower quantity of defects and vacancies created by Pb-Br anti-site and under-coordinated Pb atoms for the CsPbBr 3 NCs within CMS matrix, and significantly suppressed the nonradiative decay of the CsPbBr 3 NCs, which are similar to previously reported the perovskite@AlPO-5 and perovskite-gel composite materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation